Surgical Management of Failed Revascularization in Moyamoya Vasculopathy - Lucia, Kristin; Acker, Güliz; Schlinkmann, Nicolas; Georgiev, Stefan; Vajkoczy, Peter (Frontiers in Neurology, 2021)
Objectives: Moyamoya Vasculopathy (MMV) is a rare stenoocclusive cerebrovascular disease associated with increased risk of ischemic and hemorrhagic stroke which can be treated using surgical revascularization techniques. Despite well-established neurosurgical procedures performed in experienced centers, bypass failure associated with neurological symptoms can occur. The current study therefore aims at characterizing the cases of bypass failure and repeat revascularization at a single center. Methods: A single-center retrospective analysis of all patients treated with revascularization surgery for Moyamoya Vasculopathy between January 2007 and December 2019 was performed. Angiographic data, cerebral blood flow analysis (H2O PET or SPECT), MRI and clinical/operative data including follow-up assessments were reviewed. Results: We identified 308 MMV patients with 405 surgically treated hemispheres. Of the 405 hemispheres treated, 15 patients (3.7%) underwent repeat revascularization (median age 38, time to repeat revascularization in 60% of patients was within 1 year of first surgery). The most common cause of revascularization was a symptomatic bypass occlusion (80%). New ischemic lesions were found in 13% of patients prior to repeat revascularization. Persistence of reduced or progressive worsening of CVRC compared to preoperative status was observed in 85% of repeat revascularization cases. Intermediate-flow bypass using a radial artery graft was most commonly used for repeat revascularization (60%) followed by re-STA-MCA bypass (26%). High-Flow bypass using a saphenous vein graft as well as an occipital artery to MCA bypass were each used once. Following repeat revascularization, no new ischemic events were recorded. Conclusion: Overall, repeat revascularization is needed only in a small percentage of the cases in MMV. A rescue surgery should be considered in those with neurological symptoms and decreased CVRC. Intermediate flow bypass using a radial artery graft is a reliable technique for patients requiring repeat revascularization. Based on our institutional experience we propose an algorithm for guiding the decision process in cases of bypass failure.